Studi persepsi masyarakat tentang pengelolaan lanskap agroforestri di sekitar sub DAS Way Besai, provinsi Lampung - Christine Wulandari (Institut Pertanian Bogor, 2010)
The narrowness of the average land that belongs to the community (respondents who have a good level of perception towards agroforestry landscape management as much as 42.07%, moderate perception was 28.28% and 29.65% respondents have low level of perception. Based on this research had known that very significant factors were land size, education and the amount of training; income was significant factor, and age and occupation concluded as not significant factors.